Intoxication by Cyanide in Pregnant Sows: Prenatal and Postnatal Evaluation - André T. Gotardo; Isis M. Hueza; Helena Manzano; Viviane M. Maruo; Paulo C. Maiorka; Silvana L. Górniak (Journal of Toxicology)
Cyanide is a ubiquitous chemical in the environment and has been associated with many intoxication episodes; however, little is known about its potentially toxic effects on development. The aim of this study was to evaluate the effects of maternal exposure to potassium cyanide (KCN) during pregnancy on both sows and their offspring. Twenty-four pregnant sows were allocated into four groups that orally received different doses of KCN (0.0, 2.0, 4.0, and 6.0 mg/kg of body weight) from day 21 of pregnancy to term. The KCN-treated sows showed histological lesions in the CNS, thyroid follicle enlargement, thyroid epithelial thickening, colloid reabsorption changes, and vacuolar degeneration of the renal tubular epithelium. Sows treated with 4.0 mg/kg KCN showed an increase in the number of dead piglets at birth. Weaned piglets from all KCN-treated groups showed histological lesions in the thyroid glands with features similar to those found in their mothers. The exposure of pregnant sows to cyanide thus caused toxic effects in both mothers and piglets. We suggest that swine can serve as a useful animal model to assess the neurological, goitrogenic, and reproductive effects of cyanide toxicosis.